Русский героический эпос - Пропп Владимир Яковлевич (КоЛибри, 2021)
Экземпляры: РБаб (20240402) / Инвентарный номер: 56970 / Цена: 545.00 / Сис.шифр: 82.3(2Рос=Рус) / Авт.знак: П 81 / ББК: 82.3(2Рос=Рус)